Retropharyngeal abscess in neonate - A misdiagnosed entity - Virender Kumar Gehlawat; Kundan Mittal; Vandana Arya (Wolters Kluwer Medknow Publications, 2018)
Respiratory distress is common problem seen in new born and infants due to anatomical and physiological differences from adult. Infant can present with respiratory distress, inspiratory stridor, feeding difficulty, and cyanosis. At birth usually congenital malformation, hyaline membrane diseases, nasal block are common disorders leading to respiratory distress. Retropharyngeal abscess is uncommon in neonatal period.